Student discontinuous trajectories in the Faculty of Social Sciences - Jenny Segovia Bustos (ADIDE Federación, 2015)
The aim of this study is to quantify the proportion of students who have behavior postponement of compulsory surrender at the beginning of a college degree subjects , analyzing socio-demographic profile . The methodology is quantitative, through a longitudinal design . The results show that the behaviors associated with the postponement of surrender of activities generally occur in male students, who come from households with high educational capital average level, most do not have children and not working. These data indicate that procrastination behavior to inadequate time management are linked to the organization of academic tasks.